Strategi Guru PAI dalam Menumbuhkan Kesadaran Keagamaan Siswa Kelas XI SMA Negeri 4 Kota Bima - Yusral Anas; Ruslan; Irwan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to determine the strategies used by Islamic Religious Education (PAI) teachers in fostering students' religious awareness in class XI of SMA Negeri 4 Kota Bima. In addition, this study also wants to examine the implications of the PAI learning strategy on the development of students' religious awareness. Thus, the results of this study are expected to provide a clear picture of effective methods in improving the understanding and application of religious values among students, especially in the environment of SMA Negeri 4 Kota Bima. The type of method used in this research is a qualitative method with a descriptive approach, the data source in this study is divided into two parts, namely primary data sources and secondary data sources, where primary data sources are obtained directly from the research site in the form of interviews with PAI teachers and grade XI students at SMAN 4 Kota Bima, while secondary data researchers get from other sources in the form of journals, books and reports that are closely related to the research conducted. The results showed that the PAI teacher's strategy in fostering students' religious awareness at SMAN 4 Kota Bima includes motivation, exemplary, dialog, discussion, and provision of facilities. The implication of this strategy is the growth of religious awareness in students which can be seen from religious activities such as Dhuha prayers in congregation and Qur'anic tadarus.